Pelatihan Ecoprint untuk Pemberdayaan Ekonomi Masyarakat Desa Pelita Jaya - Frida Maryati Yusuf; Nurul Fajryani Usman; Regina Valentina Aydalina; Syam S. Kumaji (-, 2026)
The community of Pelita Jaya Village has abundant coastal plants, but their leaves, flowers, stems, and twigs had not been used as materials for products with economic value. This community service aimed to introduce ecoprint, improve practical skills, and encourage the use of local natural materials as the basis of household-scale creative products. The activity was conducted face-to-face at the Pelita Jaya Village Office on 4 May 2023 through lectures, discussions, demonstrations, direct practice, and end-of-session evaluation. Participants consisted of approximately 15 members of the village community, especially PKK women, supported by three lecturers and two students. The activity ran smoothly, participants directly practiced simple ecoprint production, and a fabric product bearing natural plant patterns was produced. The training showed that locally available plant materials can be transformed into environmentally oriented craft products and may become an initial step toward developing household economic activities.